A microcomputer-based expert system for checking verbs and articles in English sentences - Muhundan, G.; Vilas Wuwongse; Radok, J.R.M; Clink, Marsha; The Government of Australia (Bangkok : Asian Institute of Technology, 1984)
The purpose of this study is to develop a microcomputer-based expert system to detect grammatical errors in English sentences written by nonnative English speakers. The parts of speech considered are verbs and articles. The algorithm used follows reasoning first developed by Winograd and Naomi Sager. Their approaches involved using rules for sentence construction and checking wellformedness of sentences by application of restrictions. In this study these two separate parts are combined and used together. This step facilitates the implementation on microcomputers. PROLOG is used as the programming language.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1984
Keywords: Microcomputers; English language -- Grammar